Radiographic Evaluation of Iatrogenic Errors of Root Canal Treatments Performed in an Undergraduate Dental Clinic - Ensieh Grayli; Alireza Peyvandi; Maysa Mallahi; Shabnam Naeemi; Elham Afshari (Mashhad University of Medical Sciences, 2021)
Introduction: Iatrogenic errors may occur during root canal treatments (RCTs) performed by undergraduate students. The current study explores the iatrogenic errors of RCTs made by undergraduate students at Gorgan School of Dentistry, Golestan, Iran. Methods: This cross-sectional study was conducted using 236 randomly selected treatment records of RCTs performed on first molars by undergraduate dental students. Periapical radiographs were independently explored for the following errors: overfilling, underfilling, legde formation, and apical transportation. Data analysis was performed using Statistical Package for Social Sciences (SPSS) version 17.0, and a Chi-square test at the 0.05 level of significance. Results: Periapical radiographs of 236 endodontically treated first molars were assessed. The results showed that 87.1% of root canals were adequately filled to the working length. Among the teeth treated by fifth- and sixth-year students, 62.5% and 66.4% of teeth were adequately filled to the working length, respectively, resulting in no statistically significant difference (P>0.05). In respect to the prevalence of ledge formation and apical transportation errors, there was no statistical difference either between the treatments performed by fifth- and sixth-year students (P>0.05) or the location of the treated tooth (mandible or maxilla) (P>0.05). Conclusion: Within the limitations of the present study, the results showed a rather low, but non-negligible prevalence of procedural errors in RCTs performed by fifth- and six-year undergraduate students at Gorgan School of Dentistry. Prevalence of errors made by fifth- and six-year students was similar.